2020
DOI: 10.3390/antiox9070585
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of SPA0355, a Thiourea Analogue, Against Lipopolysaccharide-Induced Acute Kidney Injury in Mice

Abstract: Inflammation and oxidative stress plays an essential role in the pathophysiology of sepsis-associated acute kidney injury (AKI). SPA0355, a thiourea analogue, has been shown to display beneficial effects against a variety of inflammatory diseases arising from its anti-inflammatory and anti-oxidant properties. However, the potential protective effects of SPA0355 against lipopolysaccharide (LPS)-induced AKI have not been explored. The aim of this study was to evaluate the effects of SPA0355 on LPS-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…In our study, LPS treatment increased the amounts of lipid peroxidation products and reversed a reduction in GSH/GSSG ratio in the kidneys. These results are consistent with previous studies showing that markedly elevated levels of ROS, protein oxidation, and lipid peroxidation were detected in patients with septic AKI [20,32] and mice injected with LPS [19,20]. Interestingly, we found that oxidative stress induced by LPS was effectively alleviated by apamin.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, LPS treatment increased the amounts of lipid peroxidation products and reversed a reduction in GSH/GSSG ratio in the kidneys. These results are consistent with previous studies showing that markedly elevated levels of ROS, protein oxidation, and lipid peroxidation were detected in patients with septic AKI [20,32] and mice injected with LPS [19,20]. Interestingly, we found that oxidative stress induced by LPS was effectively alleviated by apamin.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, immune cell infiltration into injured kidneys has been known to aggravate inflammation and tissue injury [2,3]. Infiltration of multiple pro-inflammatory cells, such as macrophages and CD4 + T cells, is also commonly detected in the CLP sepsis model [39,42] and the LPS-induced AKI model [19,43]. Here, we showed that LPS-injected mice displayed increased expression of TLR4 compared to control mice.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Thin sections (4 μm) were stained with hematoxylin and eosin (H&E) or periodic acid–Schiff (PAS). The severity of tubular injury was scored semiquantitatively by estimating the percentage of damaged area: 0, 0%; 1, ≤10%; 2, 11–25%; 3, 26–45%; 4, 46–75%; and 5, 76–100% [ 32 , 33 ]. Tubular injury was analyzed in 5 randomly chosen fields at ×400 magnification per kidney sample.…”
Section: Methodsmentioning
confidence: 99%